The Viseu and Lamego clergy : clerical wills and social ties - Saraiva, Anísio Miguel de Sousa (2012)
From the documentation collated under the auspices of the Fasti Ecclesiae Portugaliae project, we selected as the object of this paper the as yet unpublished series of wills of the Viseu and Lamego Sees, penned between the years 1147 and 1325.We focusfocused on the analysis of the final wills inscribed in the testaments of the bishops, dignitaries, canons and other clergy of these two cathedrals, with a particular interest in the bequests through which these clergymen reveal some type of connection to their family group or to other social groups or networks. By means of these data, we study whether the entrance of these clergymen into the Church of Viseu and Lamego implied a breaking off from kinship ties, replacing them with new bonds of confidence and dependence established within the clergy or whether, on the contrary, these men simultaneously continued with distinct levels and modes of relationship, whether within or beyond the Church. Should this latter position be confirmed, we seek to identify the various relational networks and evaluate the influence they exerted on the clergymen’s social life, through the importance that, as testators, they ascribed to these relationships at the moment of preparing for death and dividing up their worldly possessions.